College and Career Ready: Preparing Students in Fitness and Health Literacy. (2nd September 2016) - Buskist, Connie; Reilly, Erin; Walker, Andria; Bourke, Nicholas
Abstract : The Common Core State Standards (CCSS) for English language arts have been adopted by many states across the country in an effort to prepare students for life after high school, whether that be going to college or joining the work force. The anchor standards of the CCSS, known as the College and Career Ready Standards, describe the literacy skills of college and career-ready individuals. Physical educators, as well as classroom teachers, have a role in preparing students to be literate, independent and knowledgeable adults who are able to make informed decisions as they go through life. Students' abilities to make informed choices about their health and fitness as adults depends on the knowledge and skills developed in both physical education and the regular classroom, making collaboration between these teachers essential to college and career readiness. This article describes strategies that physical educators can use to support literacy development and promote critical thinking skills for K–12 students while meeting SHAPE America's National Standards for K–12 Physical Education.